Relationship between compatibility, leisure and marital satisfaction among married Nigerians - Chioma, Regina Uzoma; Sulong, Rose Manisah (Human Resource Management Academic Research Society, 2022)
Marital satisfaction is a vital topic of study, because of the ever developing need to fortify the well-being of individuals and families. This research aims to explore the relationship between compatibility, leisure activities and marital satisfaction among Nigerian couples. The measures used in this research were the Revised Dyadic Adjustment Scale and the ENRICH Marital Satisfaction Scale. The questionnaire was distributed to married Nigerians using an online survey form. A total of 218 individuals participated in this study, but only 217 samples were analysed. The mean score suggested that there is a high level of marital satisfaction among Nigerian couples, which is consistent with the results of past studies which have investigated the levels of marital satisfaction of Nigerian couples. Multiple regression analysis was conducted to determine the influence of compatibility and leisure activities on marital satisfaction. Results show that it was a statistically significant model (F (2,214) = 20.36, p < 0.001). Compatibility (t=6.338, p<0.001) was a statistically significant predictor of marital satisfaction. Leisure activities was not a significant predictor of marital satisfaction. The proposed recommendation for future research would be to recruit a representative sample for future studies using stratified random sampling techniques to increase generalizability.